Analisis SWOT Dalam Menentukan Strategi Pemasaran Rokok Elektrik (VAPE) Pada G VAPE Jember - Shendy Andrie Wijaya; Yusita Titi Hapsari; Asalia Melandri (Perspektif Pendidikan dan Keguruan, 2023)
This study aims to examine and describe the factors that become internal strengths and weaknesses, factors that become external opportunities and threats, and determine the right marketing strategy to be applied to G Vape Jember. This research is a qualitative descriptive research. The number of respondents is 25 people, the determination of respondents in this study uses a purposive sampling technique. Data collection techniques used are observation, interviews and documentation. Data analysis in this study used data collection, data reduction, data presentation, drawing conclusions. The data validity technique uses triangulation by examining the use of sources. The results of the study show that: 1) the internal strengths and weaknesses of G Vape Jember are G Vape's strategic location, quality products sold, friendly store service, affordable prices offered to consumers, availability of member cards to get free liquid products if the purchase is 10 times. While the weaknesses of G Vape are: incomplete product variations, lack of security, lack of employees. 2) factors that become external opportunities and threats to G Vape Jember, namely the Vape Trend which is growing, Improving people's consumptive lifestyle, Technology is increasingly sophisticated. While the threats to G Vape are: More and more similar vape shops, Competitor products have competitive prices. 3) The right strategy to apply G Vape Jember in marketing its products based on SWOT analysis theory. are typically sectioned logically as an overview of what appears in the paper